LIPEDEMA: DIAGNOSTIC APPROACHES AND THERAPEUTIC STRATEGIES — A REVIEW - Nowakowska, Zofia; Burzej, Agniszka; Komenda, Maciej; Marek, Aleksandra; Dziki, Karolina; Garncarz, Katarzyna; Jamroch, Krzysztof; Kacalak, Mateusz; Szklarska-Komenda, Julia; Dybizbańska, Wiktoria (International Journal of Innovative Technologies in Social Science, 2026)
Lipedema is a chronic adipose tissue disorder characterized by disproportionate subcutaneous fat accumulation, predominantly affecting women and often emerging during periods of hormonal change. Its pathophysiology remains incompletely understood and is thought to involve genetic predisposition, hormonal influences, and lymphatic or vascular dysfunction. The condition is associated with pain, reduced mobility, and significant psychosocial burden, highlighting the need for improved recognition and management. Lipedema-related literature published between 2015 and 2025 was systematically reviewed using databases including PubMed and Google Scholar, with keywords such as lipedema, fat disorder, lymphedema, obesity, lipedema treatment, diet, weight loss, and liposuction. Meta-analyses, review articles, and original studies published in English were selected based on relevance and recency of findings. Diagnosis is primarily based on clinical evaluation supported by characteristic features such as symmetrical limb involvement, pain, easy bruising, and sparing of the hands and feet, with imaging modalities including ultrasonography, MRI, and lymphoscintigraphy serving as adjunctive tools in differential diagnosis. Management requires a multimodal approach combining patient education, conservative therapies, including compression therapy, tailored physical activity, dietary strategies and surgical interventions when indicated. Conservative treatment mainly focuses on symptom control and slowing disease progression. Liposuction, particularly water-assisted techniques, remains the only intervention capable of permanently reducing pathological adipose tissue. The aim of the work: The objective of this review is to analyze diagnostic methods for lipedema, as well as treatment strategies, including conservative therapies and surgical interventions.